Pengaruh Mindfulness-Based Learning Terhadap Fleksibilitas dalam memecahkan masalah Matematika di Sekolah Dasar - Saleh, Sitti Fithriani; Mutmainnah, Mutmainnah; Dwidelia, Nurfidhea; Azzahra, Rachel Aura (Bima Journal of Elementary Education, 2025)
The background of this research is based on the urgency to increase flexibility of thinking in solving mathematical problems at the Elementary School level. This study aims to examine the effect of Mindfulness-Based Learning (MBL) on students' flexibility of thinking in solving mathematics problems in elementary school. The research design used was quasi-experimental with a pretest-posttest non-equivalent control group design. The research sample consisted of 60 fourth and fifth grade students who were divided into two groups: an experimental group that participated in mindfulness-based learning and a control group that participated in conventional learning. Data were collected through a mathematical thinking flexibility test, a mindfulness questionnaire, and classroom observations. The results showed that the experimental group experienced a significant increase in thinking flexibility, with a higher average posttest score (85.767) than the control group (69.733), with a p-value < 0.001. The application of Mindfulness-Based Learning is proven to be effective in improving students' ability to move between various mathematical problem-solving strategies, as well as increasing awareness and focus in the problem-solving process. These findings indicate that mindfulness intervention can be an effective approach to increasing flexibility of thinking in primary school, especially in mathematics learning.